Direct Observations of Parenting and Real-time Negative Affect among Adolescent Smokers and Non-Smokers - Richmond, Melanie J. (2012)
OBJECTIVE: This longitudinal study examined how observations of parental general communication style and control with their adolescents predicted changes in negative affect over time for adolescent smokers and non-smokers. METHOD: Participants were 9(th) and 10(th) grade adolescents (N = 111; 56.8% female) who had all experimented with cigarettes and were thus at risk for continued smoking and escalation; 36% of these adolescents (n = 40) had smoked in the past month at baseline and were considered smokers in the present analyses. Adolescents participated separately with mothers and fathers in observed parent-adolescent problem-solving discussions to assess parenting at baseline. Adolescent negative affect was assessed at baseline, 6- and 24-months via ecological momentary assessment. RESULTS: Among both smoking and non-smoking adolescents, escalating negative affect significantly increased risk for future smoking. Higher quality maternal and paternal communication predicted a decline in negative affect over 1.5 years for adolescent smokers but was not related to negative affect for non-smokers. Controlling maternal, but not paternal, parenting predicted escalation in negative affect for all adolescents. CONCLUSIONS: Findings suggest that reducing negative affect among experimenting youth can reduce risk for smoking escalation. Therefore, family-based prevention efforts for adolescent smoking escalation might consider parental general communication style and control as intervention targets. However, adolescent smoking status and parent gender may moderate these effects.